2016
DOI: 10.1038/ncomms11706
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the sorghum transcriptome using single-molecule long reads

Abstract: Alternative splicing and alternative polyadenylation (APA) of pre-mRNAs greatly contribute to transcriptome diversity, coding capacity of a genome and gene regulatory mechanisms in eukaryotes. Second-generation sequencing technologies have been extensively used to analyse transcriptomes. However, a major limitation of short-read data is that it is difficult to accurately predict full-length splice isoforms. Here we sequenced the sorghum transcriptome using Pacific Biosciences single-molecule real-time long-rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
470
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 464 publications
(495 citation statements)
references
References 58 publications
21
470
4
Order By: Relevance
“…Maize has the largest collection of RNA-Seq data among the nine species examined, and also has the largest number of AS events, but the percentage of multi-exon genes that undergo AS is similar to other species. The proportions of genes that undergo AS and the total number of AS events are higher than previously reported for many plant species (Campbell et al 2006;Amborella Genome Project 2013;Walters et al 2013;Panahi et al 2014;Abdel-Ghany et al 2016). Similar to previous genome-wide AS studies Thatcher et al 2014;Chamala et al 2015;Mandadi and Scholthof 2015), IntronR was the most commonly observed AS event type in monocots.…”
Section: Resultssupporting
confidence: 69%
“…Maize has the largest collection of RNA-Seq data among the nine species examined, and also has the largest number of AS events, but the percentage of multi-exon genes that undergo AS is similar to other species. The proportions of genes that undergo AS and the total number of AS events are higher than previously reported for many plant species (Campbell et al 2006;Amborella Genome Project 2013;Walters et al 2013;Panahi et al 2014;Abdel-Ghany et al 2016). Similar to previous genome-wide AS studies Thatcher et al 2014;Chamala et al 2015;Mandadi and Scholthof 2015), IntronR was the most commonly observed AS event type in monocots.…”
Section: Resultssupporting
confidence: 69%
“…With the help of IsoSeq, an astonishing diversity of splicing events in various systems has started to emerge even in well-studied cancer cell-line systems such as MCF7 [5]. A number of other analyses in other cellular contexts have also utilized the IsoSeq assay [6][7][8][9][10][11]. Given that alternative splicing is known to be tissue and condition dependent, we hypothesized that drug administration should also alter the splicing landscape of cells as part of multifaceted cellular response to stimuli which cannot be completely captured using standard RNAseq analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This process can have phenotypic effects on par with changes in gene expression levels [37,38]. While gene expression studies using RNA sequencing generally infer patterns of alternative splicing, short-read sequencing is limited in its ability to quantify expression at the transcript level [39]. The increasing availability of longer reads [39] and improved bioinformatics tools [40] will lead to a greater understanding and appreciation of the role of alternative splicing in evolution and phenotypic outcomes.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…While gene expression studies using RNA sequencing generally infer patterns of alternative splicing, short-read sequencing is limited in its ability to quantify expression at the transcript level [39]. The increasing availability of longer reads [39] and improved bioinformatics tools [40] will lead to a greater understanding and appreciation of the role of alternative splicing in evolution and phenotypic outcomes. A globally diverse set of transcriptomes will also be useful for mapping population specific alternative splicing patterns.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%